Legal Protection of Health Workers in the Task Force for the Acceleration of Handling Covid-19 from a State Administrative Law Point of View - Santoso, Aris Prio Agus; Wahyudi, Totok; Rohmah, Safitri Nur; Haryadi, Ary Rachman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Article 28D paragraph (1) of the 1945 Constitution states that every person has the right to recognition, guarantee, protection and legal certainty that is just and equal treatment before the law, then Article 57 letter a of Law No. 36 of 2014 concerning Health Personnel also states that health workers in carrying out practices are entitled to obtain legal protection as long as carrying out their duties in accordance with Professional Standards, Professional Service Standards, and Operational Procedure Standards, but in their implementation, legal protection has not been seen to be carried out by office holders.The problem in this study is how the legal protection of health workers in the task force for acceleration of Covid-19 handling and what are the constraints of health workers in obtaining guarantees of occupational safety and health in the task force for acceleration of Covid-19 handling reviewed on administrative law.This research method uses a sociological juridical approach, by collecting data from field studies and literature studies, to find out the legal protection of health workers in the task force for handling Covid-19 acceleration reviewed on administrative law. The data obtained were analyzed qualitatively.Based on the results of the study it was found that health workers get legal protection in the form of supervision and guidance, but the legal protection efforts provided there are still weaknesses because some of the rights of health workers have not been fulfilled. In connection with the provision of occupational safety and health guarantees to health workers there are still several obstacles, including; due to the complicated bureaucracy of the Regional Government, and the uneven distribution of PPE (Personal Protective Equipment). The government, in this case, has not been able to provide maximum legal protection and work health and safety insurance for health workers.